The story of a number - Maor, Eli. (Hyderguda : University Press, 1999)
Although the story of pi has been told exhaustively, the fate of its close relative, the number e, has fared less well, despite the central role it plays in mathematics. This study, geared to readers with only a modest background in maths, describes the mathematicians involved in e's discovery
Includes bibliographical references and index.
Keywords: The number